The Existing Conditions of Tourism Destinations in Jembrana Regency, Bali - Murtono, Putu Agus (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2024)
Jembrana Regency, as one of the districts in Bali Province, has enormous tourism potential. However, most tourists' attention is still focused on areas such as Ubud, Kuta, Seminyak and Nusa Dua. Therefore, this research aims to identify tourism potential in Jembrana Regency, evaluate current conditions, and analyze the factors that influence tourism development in the Jembrana area, Bali. This research uses a qualitative methodology to identify tourism potential in Jembrana Regency, evaluate current conditions, and analyze the factors that influence tourism development in the Jembrana area, Bali with data collection techniques using structured interviews. Based on research conducted, Jembrana Regency has enormous tourism potential, both in terms of culture and natural beauty. Some of the main tourism destinations identified include Yeh Embang Village with Rambut Siwi Temple, Gilimanuk Early Human Museum, and West Bali National Park. Even though it has great potential, tourism development in Jembrana Regency is currently still not optimal. Factors that influence this include limited accessibility, inadequate infrastructure and supporting facilities, as well as a lack of effective promotion and marketing. Apart from that, the aspect of local community participation in the management and development of tourism in Jembrana also needs to be improved. Communities around tourist areas must be actively involved so they can participate in cultural and natural preservation efforts, as well as obtain economic benefits from tourism development